Sedation of hyperthyroid cats with subcutaneous administration of a combination of alfaxalone and butorphanol. Issue 4 (22nd March 2013) - Ramoo, S; Bradbury, LA; Anderson, GA; Abraham, LA
<x xml:space="preserve">Abstract</x> Objective To evaluate the sedative, respiratory and cardiovascular effects of subcutaneously administered alfaxalone and butorphanol in a group of hyperthyroid cats. Design A prospective, single‐centre observational study. Methods Client‐owned hyperthyroid cats (n = 20) were examined and sedated with alfaxalone (3 mg/kg) and butorphanol (0.2 mg/kg) administered subcutaneously. Sedation scores, heart rate, respiratory rate and blood pressure were measured at 15‐min intervals during the 45‐min observation period and compared with pre‐sedation values. At the end of 45 min, cats were assessed to be adequately sedated for oral administration of iodine‐131 if there was minimal resistance and an intact gag reflex. Results The maximum median sedation score was reached 45 min after injection. The lowest mean heart and respiratory rates and blood pressure values occurred 30 min after injection. Significant decreases were noted in respiratory rates at all three time points (P < 0.001). Systolic, diastolic and mean blood pressure measurements were also significantly decreased at 15 and 30 min after injection (P < 0.05). Conclusion Subcutaneously administered alfaxalone and butorphanol can be used for sedation in cats undergoing procedures of short duration. Blood pressure should be monitored because of transient decreases observed in some cats. Further studies are required to determine whether the sedative, respiratory and cardiovascular effects are similar in euthyroid cats.